2005
DOI: 10.1152/ajpgi.00198.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dual oxidase2 is expressed all along the digestive tract

Abstract: The dual oxidase (Duox)2 flavoprotein is strongly expressed in the thyroid gland, where it plays a critical role in the synthesis of thyroid hormones by providing thyroperoxidase with H2O2. DUOX2 mRNA was recently detected by RT-PCR and in-situ hybridization experiments in other tissues, such as rat colon and rat and human epithelial cells from the salivary excretory ducts and rectal glands. We examined Duox2 expression at the protein level throughout the porcine digestive tract and in human colon. Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
167
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(176 citation statements)
references
References 28 publications
8
167
0
1
Order By: Relevance
“…The importance of DUOX2 in thyroid hormone synthesis is supported by clinical observations of hypothyroidism in association with missense mutations in the DUOX2 gene (28,29). DUOX1 and 2 are also expressed in airway and intestinal epithelia, where they may contribute to host defense by a similar cooperative mechanism with lactoperoxidase (LPO), which is secreted by submucosal glands (1,30,31). A structurally related dual oxidase, Udx1, is expressed in sea urchin eggs and is activated upon fertilization to produce H 2 O 2 which stimulates ovoperoxidase-mediated protein cross-linking within the fertilization envelope (32).…”
Section: Targets For Nox-derived Ros: Heme Peroxidasesmentioning
confidence: 98%
“…The importance of DUOX2 in thyroid hormone synthesis is supported by clinical observations of hypothyroidism in association with missense mutations in the DUOX2 gene (28,29). DUOX1 and 2 are also expressed in airway and intestinal epithelia, where they may contribute to host defense by a similar cooperative mechanism with lactoperoxidase (LPO), which is secreted by submucosal glands (1,30,31). A structurally related dual oxidase, Udx1, is expressed in sea urchin eggs and is activated upon fertilization to produce H 2 O 2 which stimulates ovoperoxidase-mediated protein cross-linking within the fertilization envelope (32).…”
Section: Targets For Nox-derived Ros: Heme Peroxidasesmentioning
confidence: 98%
“…When mutated in such enzymes as horseradish peroxidase, cytochrome c peroxidase, and dehaloperoxidase, a significant loss of activity is observed (42)(43)(44)(45)(46). This fact has led researchers to postulate that the N-terminal region of DUOX1 may not act as a classical peroxidase but rather as a SOD (8,12). In an effort to clarify the function of these domains, now available as purified and structurally sound proteins, we examined each homolog with regard to its peroxidase and SOD activity.…”
Section: Design and Expression Of Soluble Duox1mentioning
confidence: 99%
“…DUOX1 and 2 (formerly also known as ThOX1 and 2 for thyroid oxidase) were first identified in the mammalian thyroid gland (9,10). This localization is not exclusive because both can also be found in nonthyroid tissues; DUOX1 is prominent in airway epithelial cells (11) and DUOX2 in the salivary glands and gastrointestinal tract (4,12,13). Homologs of each DUOX have also been identified in lower organisms, including Caenorhabditis elegans and Drosophila melanogaster (14).…”
mentioning
confidence: 99%
“…Interestingly, the diverse NOX and DUOX family enzymes are not only expressed in phagocytic cells, but also in various nonphagocytic cells, including mucosal epithelial cells (Ha et al, 2005;Allaoui et al, 2009;Fischer, 2009), indicating their potential biological roles in these cells. In addition, several recent studies have shown that ROS are microbicidal effector molecules in the gut epithelia (El Hassani et al, 2005;Ha et al, 2005Ha et al, , 2009a. In Drosophila, there is only one Duox gene and one Nox gene in the genome, and genetic analysis has shown that Duox-knockout flies, but not Nox-knockout flies, cannot produce infection-induced ROS (Ha et al, 2005).…”
Section: Introductionmentioning
confidence: 99%